AB1329 Biologic agents and risk of serious infections in rheumatoid arthritis, psoriatic arthritis and ankylosing spondylitis: results by integrating ten-year (X2006–2015) administrative databases in the italian region of friuli venezia giulia. (12th June 2018) - Quartuccio, L.; Zabotti, A.; Del Zotto, S.; Zanier, L.; De Vita, S.; Valent, F.
Abstract : Background: Serious infections are a major concern for patients considering biologic agents for rheumatoid arthritis (RA) or psoriatic arthritis (PsA) or ankylosing spondylitis (AS). Evidence from meta-analyses is consistent with an increased risk of serious infections with biologic disease-modifying antirheumatic drugs (bDMARDs); 1 however, long-term real-life studies are scarce and controversial. Objectives: To determine the risk of serious infections (i.e., need of hospitalisation) in patients affected by RA, psoriatic arthritis (PsA) or ankylosing spondylitis (AS), treated by bDMARDs in the Italian region of Friuli Venezia Giulia, approximately 1, 200, 000 inhabitants. Methods: The regional health information system was used as the source of data. Administrative data from the hospital discharge records database, the medical prescription database, and the database of exemptions from medical charges were linked at the individual patient level through an anonymous univocal stochastic key. A cohort of patients diagnosed for RA, PsA or AS from 2006 to 2015 was identified from specific national exemption codes (006, 045, 054) and followed up to either the end of 2015, or hospitalisation with the main discharge diagnosis of infection, as ICD-9-CM codes, or death, or change of residency out of the Region. Multivariate Cox regression was used to estimate the hazard ratio (HR) of hospitalisation associated with bDMARDs and adjusting for age, sex, Charlson's comorbidity index, calendar year, prescription of steroids and of csDMARDs. Use of bDMARDs was treated as a time-dependent variable. Results: Overall, the cohort consisted of 5596 subjects: 3216 (57, 5%) with RA, 1702 (30, 4%) with PsA, and 678 (12, 1%) with AS. Of them, 940 patients (16, 8%) had received at least one prescription of a bDMARDs during the study period. During follow-up, 193 (3, 4%) subjects were admitted to the hospital with a primary diagnosis of infection. The most frequent infections were upper and lower respiratory tract infections (86/193, 44, 5%), followed by sepsis (19/193, 9, 8%), and soft tissue and skin infections (16/193, 8, 3%). After adjusting for the abovementioned variables, when starting a bDMARD, the risk of infections was significantly increased, with an observed increased risk of almost 2-fold by the time of the bDMARD prescription (HR 1.694, 95% CI 1.158–2.478, p=0, 0066). Compared with patients<40 years if age, the elderly (>/=65 years) showed a much higher risk of infections (HR 3.919, 95% CI 2.286–6.716, p<0, 0001). Analyses stratified by disease indicated that RA, PsA, and AS patients starting biologic medications have increased risk of infection. Conclusions: By integrating the information coming from ten-year administrative databases, RA, PsA and AS patients starting bDMARDs are at high risk of serious infections. This risk is much higher in the elderly. Upper and lower respiratory tract infections are the most common infections, supporting the prevention policies by vaccination for influenza viruses and Str. pneumoniae, in particular in the elderly population. Reference: [1] Ramiro S, et al. Ann Rheum Dis. 2017;76(6):1101–1136. Disclosure of Interest: None declared